Research progress of rhizosphere microorganisms in Fritillaria L. medicinal plants - Zhou, Nong; Mei, Chun-Mei; Zhu, Xing-Yu; Zhao, Jing-Jing; Ma, Ming-Guo; Li, Wei-Dong (Frontiers in Bioengineering and Biotechnology, 2022)
The rhizosphere soil is an active place for the exchange of substances and information between plants, soils, and microorganisms. The microorganisms are inseparable from the activities of plant growth and development, metabolism, and reproduction. Fritillaria L. medicinal plants are unique Chinese medicinal materials, and the continuous cropping obstacles formed in the artificial planting process is severely harmful to the growth and development of Fritillaria L. medicinal plants. In this review article, we summarized the current species and distribution of Fritillaria L. medicinal plants in China, and analyzed the changes of microbial diversity in the rhizosphere soil of Fritillaria L. medicinal plants under long-term continuous cropping (mainly for bacteria and fungi). The fungi showed an increasing trend in the rhizosphere soil, resulting in the transition of the soil from the high-fertility "bacterial type" to the low-fertility "fungal type" with the increase of planting years. The interaction between Fritillaria L. medicinal plants and the rhizosphere microorganisms was reviewed, and the promising applications of the rhizosphere microbiome in the cultivation of Fritillaria L. medicinal plants were suggested. It expects that the review article favor the in-depth understanding of rhizosphere microorganisms in the growth, accumulation of active ingredients, and disease control of Fritillaria L. medicinal plants.